Standards: Engaging for the Future. - Wright, F.D. (Computer (00189162), 2018)
The IEEE Computer Society provides foundational standards for the benefit of consumers, industry, and government, as well as the programmers and engineers building tomorrow’s technology wonders. Participation in these standards-development projects is open to everyone.